The three-dimentional pelvic motion in the acceleration and maximum phases - Ota, K.i; Yoshida, T.; Maemura, H.; Tanigawa, S. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to investigate the mechanism of pelvic motion in the acceleration and maximum velocity phases. Eleven male sprinters performed 30 m and 60 m sprints at maximal effort and captured sprint movement at 15 m and 50 m. The contact time was significantly longer, and the angular displacement of pelvic elevation on the frontal plane was significantly greater in the acceleration phase than in the maximum velocity phase. Additionally, the angular displacement of pelvic elevation on the frontal plane showed a significantly positive correlation with the contact time and the stance length in the acceleration phase. These findings suggest that the greater pelvic frontal plane motion in the acceleration phase could increase the contact time and longer stance length.